Voci come fili: Scrittrici che narrando riparano vite (Balthazar, 2022)
The collective and seemingly asynchronous narratives of Natalie Léger give voice to women who are looking for justice. Her writing mixes a number of genres, such as fiction, self-fiction, memoir and biography, and establishes a strong narrative relationship among all the various voices. To narrate is to mend lives by weaving stories. Ideally, Léger joins the poetic efforts of both Ingrid De Kok and Karen Press.